The Use Of Structural Analytical Sintetik ( Sas) Method To Improve Students’ Ability In Writing And Reading At The Second Grade Students Of Sd Negeri 06 Perawang Barat - Parmias Parmias (Jurnal Ilmiah Pendidikan Scholastic, 2018)
This research is a Classroom Action Research (PTK).Conducted collaboratively between researchers, observers and subjects studied.The main objective of this research is to improve the ability of learners writing and reading grade 2 on ability wrote the entry through the method of SAS.The subjects of this study were all students of class II consisting of 26 students, with the composition of 13 women and 13 students.The implementation of this research was conducted in the odd semester of the 2015/2016 school year.The process of this research is conducted two cycles; the allocation of each cycle is two hours of lesson consists of four main actions namely planning, implementation, observation, and reflection. Based onobservationandVisible data processingenhancementUnderstanding the EvidenceQuantitative:Cycle1: The number of those who reached KKM 6 students (44.44%), the lesser value of the KKM 20 children (55.55%) andCycle 2:the score of student is reaching KKM 26students (97.22%).There is an increase of 52.78% onCycle 2 (learningwithMethodStructuralAnalyticSynthetic).Qualitative evidence:StudentcouldseenfromIncreasevaluestudents as more interestin doingLearning 2. Studentsmorebrave in Expression 3. LecturemoreNaturalandFun.That matterShowthatuseMethodStructuralAnalyticSynthetic) canImproveabilityof the beginning of writing.ThisMeansHypothesisproven.